Frequency and Type of Ovarian Tumors in Gynecological Women presenting to DHQ Teaching Hospital Gujranwala - Saima Iqbal, Anam Waqar, Faisal Ashraf, Iram Inam, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Ovarian cancer (OC) average lifetime risk is 1 in 70(1.4%).Ovarian cancer is diagnosed in 7300 women every year in UK and 239,000 women world wide.There are variations in incidence with ethnicity, white women have the highest incidence approximately14/100,000 where as Asian women have a lower incidence at 10/100,000. Aim: To find the frequency and different types of ovarian carcinomas in women presenting with pain lower abdomen. Methods: This cross-sectional study was conducted in the Department of Obstetrics and Gynecology, DHQ Hospital Gujranwala from1st May 2020 to 31st October 2020.A total of 282 women presenting with pain lower abdomen were included.All women underwent ultrasonography and ovarian tumors were noted as per operational definition. Patients with ovarian tumor underwent laparotomy, the specimen of tumors were collected with excision biopsies and sent for histopathological analysis. Results: The mean age of cases was 33.808±7.70 years, and the mean duration of complaint was 4.322±1.46 weeks and mean weight was 69.560±13.00 kg. Majority of the patients (82.3%) belonged to 20-40 years age groups. Ovarian Tumor was seen in 65(23%) patients. Among 65 patients with ovarian tumor, 72.3% were benign, 3.1% borderline and 24.6% were malignant. Conclusion: It was concluded that ovarian tumors were common between the 20 and 40 years of age. The frequency of Malignant neoplastic lesions was higher than the benign neoplastic lesions.